2017
DOI: 10.1310/hpj5203-207
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Direct Oral Anticoagulant Prescribing and Monitoring Pre- and Post-Implementation of a Pharmacy Protocol at a Community Teaching Hospital

Abstract: Background: Direct oral anticoagulants (DOACs) have become popular alternatives to vitamin K antagonists for the treatment and prevention of thromboembolic diseases; however, there are limited data regarding the appropriate use of DOACs in clinical practice. To ensure safety and efficacy of these medications, it is important that decisions regarding their use in patients rely on the available evidence. Objective: The purpose of this study was to evaluate the appropriateness of DOAC prescribing in adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…18,19 Furthermore, inpatient DOAC stewardship and monitoring programs have been described and found to improve appropriateness of DOAC prescribing. 20,21 In one study by Miele and colleagues, implementation of a pharmacist-driven DOAC protocol at a community hospital significantly reduced the total number of inappropriately administered DOAC doses by 57%. Our study builds upon their findings and includes a larger study population within an academic Although the focus of our findings is on the impact of a pharmacist-driven DOAC protocol, the role and importance of pharmacist education cannot be overemphasized.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Furthermore, inpatient DOAC stewardship and monitoring programs have been described and found to improve appropriateness of DOAC prescribing. 20,21 In one study by Miele and colleagues, implementation of a pharmacist-driven DOAC protocol at a community hospital significantly reduced the total number of inappropriately administered DOAC doses by 57%. Our study builds upon their findings and includes a larger study population within an academic Although the focus of our findings is on the impact of a pharmacist-driven DOAC protocol, the role and importance of pharmacist education cannot be overemphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Literature assessing pharmacist-driven interventions and protocols have shown similar improvements in the practice of evidence-based medicine. 14-18 To the best of our knowledge, this study is the first to examine pharmacist-driven interventions to improve guideline-concordant therapy surrounding the new ADA recommendations for patients with type 2 diabetes and concomitant ASCVD.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacist-driven interventions have demonstrated improvement in prescribing patterns, medication adherence, chart documentation, patient education, adverse events, and quality of life. 14-18 However, the impact of a pharmacist-driven protocol to improve prescribing of diabetes medications with cardiovascular benefit in patients with type 2 diabetes and ASCVD is unknown. The purpose of this study was to determine if the implementation of a pharmacist-driven protocol was associated with an increased proportion of patients prescribed evidence-based cardiovascular risk reduction therapy with a GLP-1 receptor agonist or SGLT-2 inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…17 Studies have demonstrated that the implementation of a pharmacist-driven DOAC service resulted in decreased inappropriate DOAC prescribing. 18…”
Section: Discussionmentioning
confidence: 99%